Answer: 2√2 - 3Explanation:The expession written properly is:
To rationalize that kind of expressions, this is to eliminate the radicals on the denominator you use conjugate rationalization.
That is, you have to multiply both numerator and denominator times the conjugate of the denominator.
The conjugate of √3+√6 is √3 - √6, so let's do it:
To help you with the solution of that expression, I will show each part.
1) Numerator: (√3 - √6) . (√3 - √6) = (√3 - √6)^2 = (√3)^2 - 2√3√6 + (√6)^2 =
= 3 - 2√18 + 6 = 9 - 6√2.
2) Denominator: (√3 + √6).(√3 - √6) = (√3)^2 - (√6)^2 = 3 - 6 = - 3
3) Then the resulting expression is:
9 - 6√2
-----------
-3
Which can be further simplified, dividing by - 3
-3 + 2√2
Answer: 2√2 - 3
Shiii it could be answer c
Answer:
C) 65,535
Step-by-step explanation:
You can add up the 8 terms ...
3, 12, 48, 192, 768, 3072, 12288, 49152
to find their sum is 65535.
_____
<em>Estimating</em>
Knowing the last term (49152) allows you to make the correct choice, since the sum will be more than that and less than double that.
_____
<em>Using the formula</em>
You know the formula for the sum of a geometric sequence is ...
S = a1(r^n -1)/(r -1)
where a1 is the first term (3), r is the common ratio (4), and n is the number of terms (8).
Filling in the values, you find the sum is ...
S = 3(4^8 -1)/(4-1) = 4^8 -1 = 65535
5p² - p - 18 = (5p +9)(p - 2)